Socialization of Scientific Attitude as an Effort to Strengthen Civic Engagement among Gen-Z in the Era of Society 5.0 - Ilham Hakiki Harahap; Panggih Nur Adi; Amin Harahap; Adila Saftri; Halimatusakdiah Halimatusakdiah (International Journal of Community Service Implementation, 2025)
This community outreach activity was carried out with the aim of providing an understanding of Generation Z known as the digital native generation who grew up in the era of technology and information. Despite having wide access to information, this generation faces challenges in civic engagement due to the crisis of national identity and low critical literacy. The population in this study were 25 students of SMK Negeri 2 Rantau Utara. The SMK students still have minimal understanding of Scientific Attitudes and Civic Engagement that grow in the digitalization era and the challenges they face in the future. The use of this socialization is expected to reduce the negative influence of digital ea and the role of Generation Z in facing these challenges. This study aims to provide an understanding and socialization of Scientific Attitudes as an effort to Strengthen Civic Engagement in the younger generation, especially Gen-Z in an effort to form a character based on Science and Pancasila with a qualitative descriptive approach. Research data were obtained through Socialization and interviews with Students of SMK Negeri 2 Rantau Utara, North Antau District, Labuhanbatu Regency using qualitative descriptive methods. Data were collected through interviews with vocational high school students and field observations, and supported by related literature studies. The results of the study indicate that Generation Z's lack of understanding of Scientific Attitudes and Civic Engagement in the current digital era. With the support of socialization, technology, and promotion, the understanding of vocational high school students can be further developed as in-depth information as an effort to strengthen Scientific Attitudes and Civic Engagement in the digital era.